THE RELIABILITY ANALYSIS OF METAL SPIRAL-FOLD SILOS (Collection of scientific works «Modern structures of metal and wood», 2024)
The term «object reliability» is given in accordance with the current standards. The two main methods for determining the reliability of building structures are presented. Specific design  features  of  spiral-fold  silos  and  a  brief  history  of  their  development  are  described.  The results  of  experimental  studies  of  spiral-  fold  silo  structures  are  presented.  The  statistical characteristics  of  bulk  materials  are  presented.  A  methodology  for  reliability  analysis  of  metal spiral-fold  silos  based  on  the  analysis  of  the  strength  reserve  with  consideration  of  the  complex stress-strain state has been developed. This methodology was used to analyze the reliability of a silo with a capacity of 1020 m 3 . The silo structure was loaded with various bulk materials, the statistical characteristics  of  which  were  analyzed.  The  results  of  determining  the  main  values  of  the parameters for the reliability analysis of the silo are presented in tabular form. In accordance with DBN B.1.2-14:2018, Table B.2, the recommended value of the safety characteristic (failure rate) β for  the  calculated  silo  (consequence  class  CC2,  structural  responsibility  category  A)  should correspond to the value β=4,27, thus, the results of the calculations confirmed that the reliability of the  considered  silo  is  ensured.  Based  on  the  results,  the  plots  of  stress and  safety  characteristics depending on the variation of characteristics of wheat were constructed. The graphs showed that the stresses in the silo wall increase with an increase in the density and lateral pressure coefficient and decrease with an increase in the coefficient of friction against the walls. The graphs show a linear tendency to decrease the safety characteristic with increasing stresses in the silo wall. The general conclusion  about  the  sufficient  reliability  of  the  structures  of  metal  spiral-fold  silos  that  were calculated according to current standards is proved.